2012
DOI: 10.1002/ange.201106786
|View full text |Cite
|
Sign up to set email alerts
|

Copper‐Catalyzed Cross‐Coupling Interrupted by an Opportunistic Smiles Rearrangement: An Efficient Domino Approach to Dibenzoxazepinones

Abstract: Unerwartete Smiles‐Umlagerung: Eine ungewöhnliche und hoch regioselektive Synthese von Dibenzoxazepinonen (siehe Schema; dbm=Dibenzoylmethan) verläuft über eine Dominosequenz, an der eine unerwartete Smiles‐Umlagerung beteiligt ist. Der Prozess eignet sich für elektronisch differenzierte Phenole und ist gut verträglich mit einer Variation der Benzamidsubstituenten. Auf der Grundlage erster mechanistischer Daten wird ein plausibler Reaktionspfad vorgeschlagen.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(2 citation statements)
references
References 44 publications
0
2
0
Order By: Relevance
“…In 2012, Snieckus described a protocol for the construction of dibenzoxazepinones. 17 It was observed that an unusual Smiles rearrangement occurred before final ring-closing process. Regardless a notable achievement, the investigation scope was limited to the reaction of substituted 2bromophenols and 2-iodobenzamides.…”
Section: Syn Lettmentioning
confidence: 99%
“…In 2012, Snieckus described a protocol for the construction of dibenzoxazepinones. 17 It was observed that an unusual Smiles rearrangement occurred before final ring-closing process. Regardless a notable achievement, the investigation scope was limited to the reaction of substituted 2bromophenols and 2-iodobenzamides.…”
Section: Syn Lettmentioning
confidence: 99%
“…For example, Grimaud reported a phenol Ugi–Smiles system for four-component reaction (Scheme a) . In 2012, a domino reaction to construct dibenzoxazepinones via copper-catalyzed Ullmann reaction, Smiles rearrangement, and ring-closing process was reported (Scheme b) . Recently, a cascade reaction of copper-catalyzed C–H etherification and C–N Smiles rearrangement to construct this skeleton was reported (Scheme c) .…”
Section: Introductionmentioning
confidence: 99%